2014
DOI: 10.3109/13561820.2014.895979
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional initiatives between the human health professions and veterinary medical students: a scoping review

Abstract: This article presents the findings of a scoping review designed to identify the extent, nature and range of literature on interprofessional education (IPE) initiatives between the human health professions and veterinary medical students, which is particularly important to advance One Health education and research. Nine published articles were identified. The websites of six universities were searched in order to collect further information. Interventions vary widely with regards to their structure and delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Powerful experiential learning can occur for both the veterinary students and other health profession students involved. A recent scoping review article 6 suggested that there is some type of IPE program in place at many veterinary colleges but that these programs are very diverse in their structure, delivery, objectives, and outcomes across institutions. IPE continues to expand in US and Canadian health professions programs.…”
Section: Introductionmentioning
confidence: 99%
“…Powerful experiential learning can occur for both the veterinary students and other health profession students involved. A recent scoping review article 6 suggested that there is some type of IPE program in place at many veterinary colleges but that these programs are very diverse in their structure, delivery, objectives, and outcomes across institutions. IPE continues to expand in US and Canadian health professions programs.…”
Section: Introductionmentioning
confidence: 99%
“…Research has included, for example: attitudes towards collaborative learning, where veterinary students taught medical students basic surgical skills 9 ; attitudes towards learning together on a small group activity regarding risk factors of a zoonotic disease 10 ; the importance of veterinarians in the context of interprofessional problem solving in disease prevention 11 ; and a scoping review of existing IPE one health initiatives, citing nine articles and six university websites. 12 The results of these studies are largely positive, suggesting changing attitudes and awareness of the importance of veterinarians and physicians working together. However, they tend to recommend further research of this substantial topic, particularly regarding validation of concepts and development of outcomes measures to evaluate the effectiveness of IPE.…”
Section: Introductionmentioning
confidence: 79%
“…However, they tend to recommend further research of this substantial topic, particularly regarding validation of concepts and development of outcomes measures to evaluate the effectiveness of IPE. 12 This paper acknowledges the importance of One Health style IPE research 13 and development, with the inclusion of veterinary professions as central members of the team.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing global disease threats such as Ebola and COVID-19, requires a shift in the educational framework of healthrelated disciplines, but in particular veterinarians and physicians. IPE as a pedagogical tool for including the principles of collaborative practice as embodied by the OH concept, provides a framework for educating future graduates of each discipline for cooperative practice [4]. The success of IPE promoting an OH approach to practice requires students to be ready to engage in interprofessional learning.…”
Section: Introductionmentioning
confidence: 99%